PELATIHAN MASSAGE PUNGGUNG UNTUK MENGURANGI INTENSITAS NYERI DISMENOREA PRIMER - Esa Risi Suazini; Lina Humaeroh; Nova Sri Rahayu; Neng Anjani; Andiny Hazar (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Women in the world who experience dysmenorrhea are 92%. Half had primary dysmenorrhea. In Indonesia, the incidence of dysmenorrhea is 64.25%. Dysmenorrhea needs special attention because it can interfere with activities, loss of concentration, health costs, and dependence on drugs. The purpose of this community service activity is to socialize back massage to reduce the intensity of dysmenorrhea pain in women, both teenagers and adults. This socialization is carried out in the form of training. The method used is lecture, question and answer, and practice. The media used are booklets and infocus. The material is presented in the form of power points and videos. The number of training participants is 10 people. After receiving the material, the training participants are required to try massage movements until they can.